Composite lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof

By using materials with different molar ratios of manganese iron phosphate positive electrode materials, small particles are filled into the voids of large particles, the problem of low compaction density is solved, the energy density is significantly improved, and the overall performance of the battery is improved.

CN119833626APending Publication Date: 2025-04-15SHENZHEN DYNANONIC CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411946069.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-15

Smart Images

  • Figure CN119833626A_ABST
    Figure CN119833626A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a composite lithium manganese iron phosphate positive electrode material as well as a preparation method and application thereof. The invention relates to a composite lithium manganese iron phosphate positive electrode material, which comprises a compound formed by at least two lithium manganese iron phosphate materials with different manganese iron molar ratios, the manganese-iron molar ratio of part of the lithium manganese-iron phosphate material is 6: 4-9: 1, and the manganese-iron molar ratio of the rest of the lithium manganese-iron phosphate material is 1: 9-4: 6; the manganese-iron molar ratio of the composite lithium manganese iron phosphate positive electrode material is 4: 6-6: 4. According to the invention, the lithium manganese iron phosphate materials with different manganese iron molar ratios are utilized to regulate and control the size of primary particles of the composite lithium manganese iron phosphate positive electrode material, and gaps of the large-particle lithium manganese iron phosphate material are filled with the small-particle lithium manganese iron phosphate material, so that the gap ratio in the composite lithium manganese iron phosphate positive electrode material can be effectively reduced; the powder compaction density is improved, so that the energy density is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a composite manganese iron phosphate lithium positive electrode material and a preparation method and application thereof. Background Art

[0002] Lithium iron phosphate (LMFP) cathode material has attracted much attention among lithium battery cathode materials due to its advantages of high stability, high safety, good cycle performance and low cost. However, it is still facing the problems of low energy density and poor low temperature performance. Lithium manganese iron phosphate material (4.1V) has a higher voltage platform than lithium iron phosphate (3.4V), and the theoretical discharge specific capacity of the two is the same, which means that the theoretical energy density of lithium manganese iron phosphate can be increased by about 20% compared with lithium iron phosphate, which solves the problem of low energy density of lithium iron phosphate to a certain extent. In addition, the low temperature performance of lithium manganese iron phosphate is better than that of lithium iron phosphate. In summary, lithium manganese iron phosphate is an important development direction to replace lithium iron phosphate materials.

[0003] However, the current application of LMFP still faces many challenges, such as electronic conductivity and Li + It has low conductivity, poor rate performance, severe Mn platform attenuation and low compaction, among which low compaction is the main reason why its actual energy density is less than the theoretical energy density.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] One object of the present invention is to provide a composite lithium iron manganese phosphate positive electrode material to solve the technical problem of low compaction density of lithium iron manganese phosphate materials in the prior art. The composite lithium iron manganese phosphate positive electrode material of the present invention has a high compaction density and can improve the energy density of the lithium iron manganese phosphate positive electrode material.

[0006] Another object of the present invention is to provide a method for preparing a composite lithium manganese iron phosphate positive electrode material, which has a simple process and is easy to operate.

[0007] Another object of the present invention is to provide a positive electrode sheet.

[0008] Another object of the present invention is to provide a battery.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0010] A composite lithium iron manganese phosphate positive electrode material, comprising a composite formed by at least two lithium iron manganese phosphate materials with different manganese-iron molar ratios; the manganese-iron molar ratio of part of the lithium iron manganese phosphate materials is 6:4-9:1, and the manganese-iron molar ratio of the remaining part of the lithium iron manganese phosphate materials is 1:9-4:6; the manganese-iron molar ratio of the composite lithium iron manganese phosphate positive electrode material is 4:6-6:4.

[0011] In some embodiments, the lithium manganese iron phosphate material is selected from a first material and a second material; the manganese-iron molar ratio of the first material is 6:4 to 9:1, and the manganese-iron molar ratio of the second material is 1:9 to 4:6; the particle size D50 of the first material is 96.6 to 100.4 nm, and the particle size D90 is 50 to 150 nm; the particle size D50 of the second material is 288.8 to 340 nm, and the particle size D90 is 200 to 350 nm.

[0012] In some embodiments, the compaction density of the composite manganese iron phosphate lithium positive electrode material is 2.30 to 2.6 g / cm 3 .

[0013] In some embodiments, the composite manganese iron phosphate lithium positive electrode material has a discharge specific capacity of 131 to 150 mAh / g under 1C conditions and a first efficiency of 92% to 95%.

[0014] A method for preparing a composite lithium iron manganese phosphate positive electrode material comprises the following steps:

[0015] Lithium manganese iron phosphate materials with high manganese iron molar ratio and low manganese iron molar ratio are prepared respectively.

[0016] At least two lithium iron manganese phosphate materials with different high and low manganese-iron molar ratios are mixed to obtain a composite lithium iron manganese phosphate positive electrode material with a target manganese-iron molar ratio.

[0017] In some embodiments, the molar ratio of the high manganese iron is 6:4 to 9:1, and the molar ratio of the low manganese iron is 1:9 to 4:6.

[0018] In some embodiments, the target manganese to iron molar ratio is 4:6 to 6:4.

[0019] In some embodiments, the mixing process includes mixing with a high-speed mixer at a rotation speed of 1200 to 1800 r / min, and the mixing process lasts for 5 to 10 hours.

[0020] In some embodiments, the steps of preparing lithium iron manganese phosphate materials with high manganese to iron molar ratio and low manganese to iron molar ratio respectively independently include: preparing a precursor using a carbon source, an iron source, a lithium source, a phosphorus source and a manganese source, and then calcining.

[0021] In some embodiments, the molar ratio of the lithium element in the lithium source, the sum of the manganese element and the iron element in the manganese source and the iron source, and the phosphorus element in the phosphorus source is (0.95-1.08):1:(1-1.05).

[0022] In some embodiments, the carbon source accounts for 3% to 15% by mass of the precursor.

[0023] In some embodiments, the carbon source includes at least one of glucose, fructose, sucrose, starch, lactic acid, citric acid, dextrin, chitosan and polyethylene glycol.

[0024] In some embodiments, the raw materials for preparing the precursor further include a doping source, and the doping source includes at least one of a titanium source, a magnesium source, a vanadium source, a nickel source, a niobium source, a zirconium source, and a cobalt source.

[0025] In some embodiments, the raw materials for preparing the precursor also include a doping source, the doping source includes a titanium source, and the titanium source includes at least one of titanium dioxide, titanium tetrachloride, titanium nitride, ammonium titanate, ethyl titanate, tetraethyl titanate, butyl titanate, tetraisopropyl titanate, isopropyl titanate and titanium tetraisopropoxide.

[0026] In some embodiments, the raw material for preparing the precursor further includes a doping source, the doping source includes a titanium source, and the molar amount of the titanium element in the titanium source accounts for 0.5% to 3% of the molar amount of the iron element in the iron source.

[0027] In some embodiments, during the preparation of the lithium manganese iron phosphate material with a high manganese to iron molar ratio, the molar ratio of the manganese source and the iron source, calculated as manganese element and iron element, is controlled to be 6:4 to 9:1; during the preparation of the lithium manganese iron phosphate material with a low manganese to iron molar ratio, the molar ratio of the iron source and the iron source, calculated as manganese element and iron element, is controlled to be 1:9 to 4:6.

[0028] In some embodiments, the method for preparing the precursor specifically comprises: first mixing and sand-milling the carbon source, iron source, lithium source, phosphorus source, manganese source and solvent, and then drying.

[0029] In some embodiments, the calcination treatment includes primary calcination and secondary calcination; the temperature of the primary calcination is 300-600°C, and the time of the primary calcination is 3-10 hours; the temperature of the secondary calcination is 700-900°C, and the time of the secondary calcination is 4-12 hours.

[0030] In some embodiments, the calcination process is performed under protective gas conditions.

[0031] A positive electrode sheet comprises the composite lithium iron manganese phosphate positive electrode material or the composite lithium iron manganese phosphate positive electrode material prepared by the preparation method of the composite lithium iron manganese phosphate positive electrode material.

[0032] A battery comprises the positive electrode sheet.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) The composite lithium iron manganese phosphate positive electrode material of the present invention uses lithium iron manganese phosphate materials with different manganese-iron molar ratios to control the size of the primary particles of the composite lithium iron manganese phosphate positive electrode material. The primary particles of the lithium iron manganese phosphate material with a high manganese-iron molar ratio are smaller, and the primary particles of the lithium iron manganese phosphate material with a low manganese-iron molar ratio are larger. The lithium iron manganese phosphate materials with different manganese-iron molar ratios are compounded, and the small particles of the lithium iron manganese phosphate material are filled into the voids of the large particles of the lithium iron manganese phosphate material to form a particle grading, which can effectively reduce the void ratio in the composite lithium iron manganese phosphate positive electrode material, improve its powder compaction density, and thus significantly improve its energy density.

[0035] (2) The preparation method of the composite manganese iron phosphate lithium positive electrode material of the present invention is simple and easy, and the materials can be mixed. The obtained composite manganese iron phosphate lithium positive electrode material has a high compaction density and a high energy density.

[0036] (3) The battery of the present invention has excellent cycle performance, rate performance and safety performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0038] Figure 1 X-ray diffraction patterns of the composite lithium iron manganese phosphate positive electrode materials of Examples 1 to 3 of the present invention and the lithium iron manganese phosphate positive electrode material of Comparative Example 1;

[0039] Figure 2 This is a scanning electron microscope image of the composite lithium iron manganese phosphate positive electrode material of Example 1 of the present invention;

[0040] Figure 3 This is a scanning electron microscope image of the composite lithium iron manganese phosphate positive electrode material of Example 2 of the present invention;

[0041] Figure 4 This is a scanning electron microscope image of the composite lithium iron manganese phosphate positive electrode material of Example 3 of the present invention;

[0042] Figure 5 This is a scanning electron microscope image of the lithium manganese iron phosphate material LMFP-64 of the present invention;

[0043] Figure 6 This is a scanning electron microscope image of the lithium manganese iron phosphate material LMFP-28 of the present invention;

[0044] Figure 7 This is a scanning electron microscope image of the lithium iron manganese phosphate positive electrode material of Comparative Example 1 of the present invention;

[0045] Figure 8 This is a particle size distribution diagram of the composite lithium iron manganese phosphate positive electrode material of Example 1 of the present invention;

[0046] Fig. 9 This is a particle size distribution diagram of the composite lithium iron manganese phosphate positive electrode material of Example 2 of the present invention;

[0047] Fig.10 This is a particle size distribution diagram of the composite lithium iron manganese phosphate positive electrode material of Example 3 of the present invention;

[0048] Fig.11 This is a particle size distribution diagram of the lithium manganese iron phosphate material LMFP-64 of Example 2 of the present invention;

[0049] Fig.12 This is a particle size distribution diagram of the lithium manganese iron phosphate material LMFP-28 of Example 2 of the present invention;

[0050] Fig.13 This is a particle size distribution diagram of the lithium iron manganese phosphate positive electrode material of Comparative Example 1 of the present invention;

[0051] Fig.14 The charge and discharge curves of the battery prepared by the composite lithium iron manganese phosphate positive electrode material of Examples 1 to 3 of the present invention and the lithium iron manganese phosphate positive electrode material of Comparative Example 1 at 0.1C;

[0052] Fig.15 The charge and discharge curves of the battery prepared with the composite lithium iron manganese phosphate positive electrode materials of Examples 1 to 3 of the present invention and the lithium iron manganese phosphate positive electrode material of Comparative Example 1 at 1C. DETAILED DESCRIPTION

[0053] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0054] According to one aspect of the present invention, the present invention relates to a composite lithium iron manganese phosphate positive electrode material, including a composite formed by at least two lithium iron manganese phosphate materials with different manganese-iron molar ratios; the manganese-iron molar ratio of some lithium iron manganese phosphate materials is 6:4 to 9:1, and the manganese-iron molar ratio of the remaining lithium iron manganese phosphate materials is 1:9 to 4:6; the manganese-iron molar ratio of the composite lithium iron manganese phosphate positive electrode material is 4:6 to 6:4.

[0055] The present invention utilizes lithium iron manganese phosphate materials with different manganese-iron molar ratios to control the size of primary particles of the composite lithium iron manganese phosphate positive electrode material. The primary particles of the lithium iron manganese phosphate material with a high manganese-iron molar ratio are smaller, and the primary particles of the lithium iron manganese phosphate material with a low manganese-iron molar ratio are larger. The lithium iron manganese phosphate materials with different manganese-iron molar ratios are compounded, and small particles of the lithium iron manganese phosphate material are filled into the voids of large particles of the lithium iron manganese phosphate material to form a particle grading, which can effectively reduce the void ratio in the composite lithium iron manganese phosphate positive electrode material, improve its powder compaction density, and thus significantly improve its energy density.

[0056] In some embodiments, the molar ratio of manganese to iron in some lithium manganese iron phosphate materials is, for example, 6:4, 7:3, 8:2, 9:1, etc. The molar ratio of manganese to iron in some lithium manganese iron phosphate materials is, for example, 1:9, 2:8, 3:7, 4:6, etc. In some embodiments, the molar ratio of manganese to iron in the composite lithium manganese iron phosphate positive electrode material is, for example, 4:6, 4.5:5.5, 5:5, 5.5:4.5 or 6:4, etc.

[0057] In some embodiments, the lithium manganese iron phosphate material is selected from a first material and a second material; the manganese iron molar ratio of the first material is 6:4 to 9:1, and the manganese iron molar ratio of the second material is 1:9 to 4:6; the particle size D50 of the first material is 96.6 to 100.4 nm, such as 96.6 nm, 97 nm, 98 nm, 99 nm or 100 nm, etc. The particle size D90 is 50 to 150 nm, such as 50 nm, 60 nm, 70 nm, 80 nm, 100 nm, 120 nm, 150 nm, etc. The particle size D50 of the second material is 288.8 to 340 nm, such as 288.8 nm, 290 nm, 300 nm, 310 nm, 320 nm, 330 nm, 340 nm, etc.; the particle size D90 is 200 to 350 nm, such as 200 nm, 280 nm, 250 nm, 280 nm, 300 nm, 350 nm, etc. The first material and the second material of the present invention are matched with each other in suitable particle sizes, and thus can work together to improve the compaction density of the composite manganese iron phosphate lithium positive electrode material.

[0058] In some embodiments, the composite manganese iron phosphate lithium positive electrode material has a high compaction density of 2.30 to 2.6 g / cm 3 , for example 2.30g / cm 3, 2.35g / cm 3 , 2.42g / cm 3 , 2.5g / cm 3 , 2.55g / cm 3 , 2.58g / cm 3 or 2.6 g / cm 3 etc., or any range between them.

[0059] In some embodiments, the discharge specific capacity of the composite manganese iron phosphate lithium cathode material under 1C conditions is 131 to 150 mAh / g, such as 131 mAh / g, 135 mAh / g, 140 mAh / g, 142 mAh / g, 145 mAh / g, 150 mAh / g, etc. The first efficiency is 92% to 95%, such as 92%, 93%, 94% or 95%, etc. The composite manganese iron phosphate lithium cathode material of the present invention has the characteristics of high capacity and high first efficiency.

[0060] According to another aspect of the present invention, the present invention also relates to a method for preparing the composite manganese iron phosphate lithium positive electrode material as above, comprising the following steps:

[0061] Lithium manganese iron phosphate materials with high manganese iron molar ratio and low manganese iron molar ratio are prepared respectively.

[0062] At least two of the above-mentioned lithium iron manganese phosphate materials with different high and low manganese-iron molar ratios are mixed to obtain a composite lithium iron manganese phosphate positive electrode material with a target manganese-iron molar ratio.

[0063] The preparation method of the composite lithium iron manganese phosphate positive electrode material of the present invention is simple and easy, and at least two lithium iron manganese phosphate materials with different high and low manganese iron molar ratios are mixed. The obtained composite lithium iron manganese phosphate positive electrode material has a high compaction density and high energy density.

[0064] In some embodiments, the high manganese iron molar ratio is 6:4 to 9:1 (e.g., 6:4, 7:3, 8:2, 9:1, etc.), and the low manganese iron molar ratio is 1:9 to 4:6 (e.g., 4:6, 4.5:5.5, 5:5, 5.5:4.5, or 6:4, etc.). In some embodiments, the target manganese iron molar ratio is 4:6 to 6:4 (e.g., 4:6, 4.5:5.5, 5:5, 5.5:4.5, or 6:4, etc.).

[0065] In some embodiments, the mixing process includes mixing with a high speed mixer at a speed of 1200 to 1800 r / min, such as 1200 r / min, 1300 r / min, 1400 r / min, 1500 r / min, 1600 r / min, 1800 r / min, etc., or any range between the two. The mixing time is 5 to 10 hours, such as 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, etc. The present invention adopts appropriate mixing conditions to ensure that the materials are fully mixed and the electrochemical properties of the final manganese iron phosphate lithium positive electrode material are ensured.

[0066] In some embodiments, the steps of preparing lithium iron manganese phosphate materials with high manganese iron molar ratio and low manganese iron molar ratio respectively independently include: preparing a precursor using a carbon source, an iron source, a lithium source, a phosphorus source and a manganese source, and then calcining. Wherein, by controlling the Mn / Fe molar ratio of the manganese source and the iron source, lithium iron manganese phosphate materials with different manganese iron molar ratios are obtained.

[0067] In some embodiments, the molar ratio of the lithium element in the lithium source, the sum of the manganese element and the iron element in the manganese source and the iron source, and the phosphorus element in the phosphorus source is (0.95-1.08):1:(1-1.05), for example, 0.95:1:1, 0.98:1:1.01, 1:1:1.01, 1.05:1:1.02, 1.08:1:1.05, etc.

[0068] In some embodiments, the mass percentage of the carbon source in the precursor is 3% to 15%, such as 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%, or any range between the two. In some embodiments, the carbon source includes at least one of glucose, fructose, sucrose, starch, lactic acid, citric acid, dextrin, chitosan and polyethylene glycol, such as a combination of fructose and sucrose, a combination of citric acid and dextrin, a combination of dextrin, chitosan and polyethylene glycol, etc. The present invention uses a carbon source of appropriate type and proportion, which is more conducive to improving the electrochemical properties of lithium manganese iron phosphate materials.

[0069] In some embodiments, the lithium source includes at least one of lithium dihydrogen phosphate, lithium hydroxide, lithium carbonate, lithium acetate, lithium phosphate and lithium nitrate, such as lithium dihydrogen phosphate and lithium hydroxide, lithium carbonate and lithium acetate, lithium acetate, lithium phosphate and lithium nitrate.

[0070] In some embodiments, the phosphorus source includes at least one of diammonium hydrogen phosphate, diammonium hydrogen phosphate, dipotassium hydrogen phosphate, sodium dihydrogen phosphate, phosphoric acid, iron phosphate and lithium dihydrogen phosphate, such as a combination of diammonium hydrogen phosphate and dipotassium hydrogen phosphate, a combination of iron phosphate and lithium dihydrogen phosphate, a combination of diammonium hydrogen phosphate, dipotassium hydrogen phosphate and sodium dihydrogen phosphate, etc.

[0071] In some embodiments, the manganese source includes at least one of manganese acetate tetrahydrate, manganese oxalate, manganese tetraoxide, manganese dioxide, manganese carbonate, manganese sulfate, manganese chloride, and ammonium manganate, such as manganese acetate tetrahydrate and manganese oxalate, manganese dioxide and manganese carbonate, manganese carbonate, manganese sulfate, and manganese chloride.

[0072] In some embodiments, the raw material for preparing the precursor also includes a doping source, and the doping source includes at least one of a titanium source, a magnesium source, a vanadium source, a nickel source, a niobium source, a zirconium source, and a cobalt source, such as a combination of a niobium source and a zirconium source, a combination of a magnesium source, a vanadium source, and a nickel source. In some embodiments, the titanium source includes at least one of titanium dioxide, titanium tetrachloride, titanium nitride, ammonium titanate, ethyl titanate, tetraethyl titanate, butyl titanate, tetraisopropyl titanate, isopropyl titanate, and titanium tetraisopropoxide. For example, a combination of titanium tetrachloride and titanium nitride, a combination of butyl titanate, tetraisopropyl titanate, and isopropyl titanate. In some embodiments, the molar amount of titanium in the titanium source accounts for 0.5% to 3% of the molar amount of iron in the iron source, such as 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, etc., or any range between the two. The present invention uses a titanium source of a type and a suitable dosage ratio, thereby optimizing the electrochemical properties of lithium manganese iron phosphate materials.

[0073] In some embodiments, during the preparation of the lithium iron manganese phosphate material with a high manganese-iron molar ratio, the molar ratio of the iron source and the iron source in terms of manganese element and iron element is controlled to be 6:4 to 9:1 (for example, 6:4, 7:3, 8:2 or 9:1, etc.); during the preparation of the lithium iron manganese phosphate material with a low manganese-iron molar ratio, the molar ratio of the iron source and the iron source in terms of manganese element and iron element is controlled to be 1:9 to 4:6 (for example, 1:9, 2:8, 3:7, 3.5:6.5, 4:6, etc.).

[0074] In some embodiments, the preparation method of the precursor includes but is not limited to a liquid phase method, a solid phase method and a gel method.

[0075] In some embodiments, the preparation method of the precursor specifically includes: first mixing and sand milling a carbon source, an iron source, a lithium source, a phosphorus source, a manganese source and a solvent to obtain a slurry, and then drying. In some embodiments, the speed of the first mixing is 200 to 600 r / min, such as 200 r / min, 250 r / min, 300 r / min, 350 r / min, 400 r / min, 450 r / min, 500 r / min, 550 r / min, 600 r / min, etc.; the time is 0.5 to 2 h, such as 0.5 h, 1 h, 1.5 h, 2 h, etc. In some embodiments, the solvent includes water. Using appropriate first mixing conditions and sand milling to obtain a slurry of suitable particle size is conducive to subsequent drying and calcination. In some embodiments, the particle size D50 of the material in the slurry is 0.32 to 0.34 μm, such as 0.32 μm, 0.33 μm, 0.34 μm, etc. In some embodiments, drying includes spray drying, and the drying temperature is 140-250° C., such as 140° C., 150° C., 160° C., 180° C., 200° C., 210° C., 220° C., 230° C., 250° C., etc., or any range therebetween. The present invention adopts appropriate spray drying conditions to obtain high-quality precursor particles.

[0076] In some embodiments, the calcination treatment includes primary calcination and secondary calcination; the temperature of the primary calcination is 300-600°C, such as 300°C, 320°C, 350°C, 370°C, 400°C, 450°C, 500°C, 550°C, 600°C, etc., or any range between the two. The time of the primary calcination is 3-10h, such as 3h, 5h, 8h or 10h, etc. The temperature of the secondary calcination is 700-900°C, such as 700°C, 750°C, 800°C, 850°C, 900°C, etc., or any range between the two; the time of the secondary calcination is 4-12h, such as 4h, 5h, 7h, 10h or 12h, etc. The first calcination and the second calcination are carried out under protective gas conditions, such as nitrogen and argon. The heating rate of the first calcination is 3 to 15°C / min, such as 3°C / min, 5°C / min, 8°C / min, 10°C / min or 15°C / min. The heating rate of the second calcination is 5 to 15°C / min, such as 5°C / min, 8°C / min, 10°C / min or 15°C / min. The calcined material is cooled naturally. The present invention adopts appropriate first calcination and second calcination conditions to ensure that the lithium manganese iron phosphate material has appropriate physical properties and electrochemical properties, so as to improve the electrochemical properties of the final lithium manganese iron phosphate positive electrode material.

[0077] According to another aspect of the present invention, the present invention also relates to a positive electrode sheet, comprising the above-mentioned composite lithium iron manganese phosphate positive electrode material, or the composite lithium iron manganese phosphate positive electrode material prepared by the above-mentioned method.

[0078] The positive electrode sheet of the present invention comprises a positive electrode current collector and a positive electrode material layer arranged on at least one side surface of the positive electrode current collector; the positive electrode material layer comprises the above-mentioned composite manganese iron lithium phosphate positive electrode material, a conductive agent and a binder.

[0079] According to another aspect of the present invention, the present invention also relates to a battery, comprising a positive electrode sheet.

[0080] The battery of the present invention has excellent cycle performance, rate performance and safety performance.

[0081] In some embodiments, the battery of the present invention includes the above-mentioned positive electrode sheet, negative electrode sheet, separator and electrolyte.

[0082] In some embodiments, the preparation method of the battery includes: mixing a composite manganese iron phosphate lithium positive electrode material, a conductive agent, a binder and a solvent, stirring the mixture at a rate of 400 to 500 r / min for 1.5 to 2.5 hours in a ball mill to obtain a positive electrode slurry for a lithium ion battery, and then spreading the slurry on an aluminum foil through a coating machine, and drying it at 100 to 130° C. for 5 to 10 minutes, then rolling the coated pole piece at 10 to 13 MPa, cutting it, and weighing it to calculate the mass of the positive electrode active material coated on the pole piece. The pole piece prepared above is bonded to the positive electrode shell with a conductive glue to form the positive electrode part of the lithium ion battery, and then the metal lithium sheet is used as the negative electrode and the LiPF6 solution is used as the electrolyte, and the above materials are assembled into a button battery in a glove box with O2 and H2O contents less than 0.1ppm.

[0083] According to another aspect of the present invention, the present invention also relates to an electric device, comprising the battery. The electric device of the present invention includes electric vehicles, electric tools, laptop computers, etc.

[0084] The following is a collection of specific embodiments and comparative examples to further explain the invention.

[0085] Example 1

[0086] A method for preparing a composite lithium iron manganese phosphate positive electrode material comprises the following steps:

[0087] (a) 0.6 mol of a carbon source, 0.4 mol of an iron source, 0.52 mol of a lithium source, 1.0 mol of a phosphorus source, 0.6 mol of a manganese source, 0.005 mol of a titanium source and a solvent (water) are mixed and sand-milled, wherein the carbon source is glucose, the iron source is ferric nitrate nonahydrate, the phosphorus source is ammonium dihydrogen phosphate, the titanium source is titanium dioxide, the first lithium source is lithium carbonate, and the manganese source is manganese acetate tetrahydrate. The mixing speed is 300 r / min, and the time is 1 h to obtain a slurry, and the D50 particle size of the material of the slurry is 0.33 μm. The slurry was spray dried at 200°C to obtain a precursor, which was then calcined in a nitrogen atmosphere. The first calcination was calcined at 550°C for 3 hours to remove water from the mixture and preliminarily form lithium manganese iron phosphate crystals from the lithium manganese iron phosphate precursor. The second calcination was then carried out: the temperature was raised to 700°C and maintained for 8 hours. The heating rate during the calcination process was 5°C / min, and the first material was obtained, recorded as LMFP-64-1.

[0088] (b) 0.6 mol carbon source, 0.8 mol iron source, 0.52 mol lithium source, 1.0 mol phosphorus source, 0.2 mol manganese source, 0.005 mol titanium source and solvent (water) are mixed and sand-milled, wherein the carbon source is glucose, the iron source is ferric nitrate nine hydrate, the phosphorus source is ammonium dihydrogen phosphate, the titanium source is titanium dioxide, the lithium source is lithium carbonate, and the manganese source is manganese acetate tetrahydrate. The mixing speed is 300 r / min, and the time is 1 h to obtain a slurry, and the D50 particle size of the slurry material is 0.33 μm. The slurry is spray-dried at a temperature of 200° C. to obtain a precursor, and then calcined in a nitrogen atmosphere: calcined at 550° C. for 3 h to remove water from the mixture and preliminarily form lithium manganese iron phosphate precursor into lithium manganese iron phosphate crystals, and then the temperature is raised to 700° C. and maintained for 8 h. The heating rate during the calcination process is 5° C. / min to obtain a second material, recorded as LMFP-28-1.

[0089] (c) The first material and the second material were stirred in a high-speed mixer at a mass ratio of 1:1 at a speed of 1300 r / min for 8 min to obtain a composite lithium manganese iron phosphate positive electrode material, which was recorded as LMFP-46-A.

[0090] Example 2

[0091] A method for preparing a composite lithium manganese iron phosphate positive electrode material, which differs from Example 1 in that:

[0092] The temperature of the secondary calcination in step (a) is 750° C., and a first material is prepared, which is recorded as LMFP-64-2.

[0093] The temperature of the secondary calcination in step (b) is 750° C., and a second material is prepared, which is recorded as LMFP-28-2.

[0094] (c) The first material and the second material were stirred in a high-speed mixer at a mass ratio of 1:1 at a speed of 1300 r / min for 8 min to obtain a composite lithium manganese iron phosphate positive electrode material, which was recorded as LMFP-46-B.

[0095] Example 3

[0096] A method for preparing a composite lithium manganese iron phosphate positive electrode material, which differs from Example 1 in that:

[0097] The temperature of the secondary calcination in step (a) is 780° C. to prepare the first material, which is recorded as LMFP-64-3.

[0098] The temperature of the secondary calcination in step (b) is 780° C. to prepare a second material, which is recorded as LMFP-28-3.

[0099] (c) The first material and the second material were stirred in a high-speed mixer at a mass ratio of 1:1 at a speed of 1300 r / min for 8 min to obtain a composite lithium manganese iron phosphate positive electrode material, which was recorded as LMFP-46-C.

[0100] Example 4

[0101] A method for preparing a composite lithium manganese iron phosphate positive electrode material, which differs from Example 2 in that:

[0102] In step (a), the iron source is 0.4 mol and the manganese source is 0.6 mol, and the first material is prepared, which is recorded as LMFP-64-2.

[0103] In step (b), the iron source is 0.6 mol and the manganese source is 0.4 mol, and a second material is prepared, which is recorded as LMFP-46-4.

[0104] In step (c), the first material and the second material are stirred in a high-speed mixer at a mass ratio of 1:1 at a speed of 1300 r / min for 8 minutes to obtain a composite lithium manganese iron phosphate positive electrode material, which is recorded as LMFP-55-D.

[0105] Example 5

[0106] A method for preparing a composite lithium manganese iron phosphate positive electrode material, which differs from Example 2 in that:

[0107] In step (a), the iron source is 0.2 mol, the manganese source is 0.8 mol, and the first material is prepared, which is recorded as LMFP-82-5.

[0108] In step (b), the iron source is 0.6 mol and the manganese source is 0.4 mol, and a second material is prepared, which is recorded as LMFP-46-5.

[0109] In step (c), the first material and the second material are stirred in a high-pressure mixer at a mass ratio of 1:1 at a speed of 1300 r / min for 8 minutes to obtain a composite lithium manganese iron phosphate positive electrode material, which is recorded as LMFP-64-E.

[0110] Comparative Example 1

[0111] A method for preparing a lithium manganese iron phosphate positive electrode material comprises the following steps:

[0112] 0.6mol carbon source, 0.6mol iron source, 0.52mol lithium source, 1.0mol phosphorus source, 0.4mol manganese source, 0.005mol titanium source and solvent are mixed and sand-milled, wherein the carbon source is glucose, the iron source is ferric nitrate nine hydrate, the phosphorus source is ammonium dihydrogen phosphate, the titanium source is titanium dioxide, the lithium source is lithium carbonate, and the manganese source is tetrahydrate manganese acetate. The mixing speed is 300r / min, the time is 1h, and a slurry is obtained, and the D50 particle size of the slurry material is 0.33μm. The slurry is spray-dried at a temperature of 200°C to obtain a precursor, and then calcined in a nitrogen atmosphere, the first calcination: calcined at 550°C for 3h to remove water from the mixture and preliminarily form lithium manganese iron phosphate crystals from the lithium manganese iron phosphate precursor, and then a second calcination is performed: the temperature is raised to 700°C and maintained for 8h, and the heating rate during the calcination process is 5°C / min to obtain LMFP-46 material.

[0113] Experimental example

[0114] 1. Spectral analysis and performance test of lithium manganese iron phosphate cathode material

[0115] The X-ray diffraction patterns of the lithium manganese iron phosphate positive electrode materials of Comparative Example 1 and Example 3 are as follows: Figure 1 As shown, the diffraction peak positions of the positive electrode materials prepared in Comparative Example 1 and Example 3 are consistent with the diffraction peaks of the lithium manganese phosphate standard card (PDF#13-0336), which confirms that the lattice structure of the positive electrode materials prepared in Comparative Example 1 and Example 3 is consistent with that of lithium iron manganese phosphate, and there are no impurity peaks. The samples prepared in Comparative Example 1 and Example 3 are all lithium iron manganese phosphate materials.

[0116] The ICP test results are shown in Table 1. It can be seen that in the composite manganese iron phosphate lithium positive electrode materials of Comparative Example 1 and Example 3, Mn:Fe=2:3, indicating that the prepared manganese iron phosphate lithium positive electrode material is LMFP-46 type.

[0117] Table 1ICP test results

[0118] Group Li(%) Mn(%) Fe(%) P(%) Chemical formula Comparative Example 1 4.46 13.6 19.96 18.83 <![CDATA[Li 1.062 Mn 0.409 Fe 0.591 PO4(1.005)]]> Example 1 4.44 13.7 19.90 19.08 <![CDATA[Li 1.057 Mn 0.411 Fe 0.589 PO4(1.018)]]> Example 2 4.54 13.3 19.67 19.49 <![CDATA[Li 1.102 Mn 0.407 Fe 0.593 PO4(1.059)]]> Example 3 4.44 12.9 19.89 19.08 <![CDATA[Li 1.081 Mn 0.397 Fe 0.602 PO4(1.041)]]> Example 4 4.54 17.52 17.58 19.39 <![CDATA[Li 1.033 Mn 0.503 Fe 0.497 PO4(0.990)]]> Example 5 4.56 20.35 14.11 19.40 <![CDATA[Li 1.054 Mn 0.595 Fe 0.405 PO4(1.005)]]>

[0119] The positive electrode materials in Examples 1 to 3 and Comparative Example 1 were further examined by scanning electron microscopy. The scanning electron microscopy image of the composite lithium manganese iron phosphate positive electrode material in Example 1 is as follows: Figure 2 As shown; the scanning electron microscope image of the composite lithium manganese iron phosphate positive electrode material of Example 2 is as shown Figure 3 As shown; the scanning electron microscope image of the composite lithium manganese iron phosphate positive electrode material of Example 3 is as shown Figure 4 As shown; the scanning electron microscope image of lithium manganese iron phosphate material LMFP-64 is as follows Figure 5 The scanning electron microscope image of lithium manganese iron phosphate material LMFP-28 is shown in Figure 6 The scanning electron microscope image of the lithium manganese iron phosphate positive electrode material of Comparative Example 1 is shown in Figure 7 The particle size distribution of the positive electrode materials of each embodiment and comparative example is shown in Figure 8 , Fig. 9 , Fig.10 , Fig.11 , Fig.12 , Fig.13 As shown in Table 2. It can be seen that the particle morphology of the lithium manganese iron phosphate positive electrode material prepared in Comparative Example 1 is irregular, and the average particle size is about 104nm. Compared with Comparative Example 1, the primary particles of the composite lithium manganese iron phosphate positive electrode material of Examples 1 to 3 have higher sphericity. In addition, the primary particles of the lithium manganese iron phosphate positive electrode material prepared in Comparative Example 1 are mainly concentrated in the range of 80-120nm, while the primary particle size of LMFP prepared in Examples 1-3 is mainly concentrated in the range of 120-160nm, and the primary particle size is larger than that of LMFP-46 in Comparative Example 1. This may be because the Mn content in the LMFP-28 type lithium manganese iron phosphate prepared in Examples 1-3 is relatively low, resulting in the primary particles of LMFP-28 type lithium manganese iron phosphate being larger than LMFP-46 in Comparative Example 1. The LMFP-46 lithium manganese iron phosphate prepared in Example 1 has fewer primary particles with a primary particle size in the range of 0-80 nm. This may be because the smaller primary particles are filled into the voids of the larger particles, so that the scanning electron microscope image fails to effectively capture the small particles in the voids.

[0120] Table 2 Primary particle size distribution

[0121]

[0122]

[0123] Further, conventional test results show that the finished carbon content of the LMFP-46 type high-compacted lithium manganese iron phosphate of Comparative Example 1 and Example 3 is about 1.4%, but the compaction of the lithium manganese iron phosphate of Comparative Example 1 is significantly lower than that of each example, as shown in Table 3. The lithium manganese iron phosphate material with a high manganese iron molar ratio prepared in each example has a smaller primary particle size than the LMFP-46 in Comparative Example 1, and the lithium manganese iron phosphate material with a low manganese iron molar ratio prepared in the example has a larger primary particle size than the LMFP-46 in Comparative Example 1. After the two types of lithium manganese iron phosphate materials are compounded, the lithium manganese iron phosphate with small particles is filled into the gaps of the lithium manganese iron phosphate with large particles, so that the compaction of the obtained composite lithium manganese iron phosphate positive electrode material is significantly improved.

[0124] In addition, for the higher proportion of manganese in Examples 4 and 5, their compaction should generally be lower than that of LMFP-46 in Comparative Example 1, but Examples 4-5 of the present application are prepared by compounding, and Comparative Example 1 is a straight-sprouted material, which adds a variable factor to the change in compaction. The compaction of Example 4 is higher than that of Comparative Example 1 because the proportion of manganese iron in the two is similar, which can highlight the advantages of compounding; the compaction of Example 5 is lower than that of Comparative Example 1 because the proportion of manganese iron in the two is too large, and even the optimization method of compounding is difficult to break the gap between the levels.

[0125] Table 3 Carbon content and compaction density test results

[0126] Group C% <![CDATA[Compaction (g cm -3 )]]> Example 1 1.42 2.42 Example 2 1.45 2.56 Example 3 1.41 2.47 Example 4 1.44 2.37 Example 5 1.42 2.32 LMFP-28-2 1.43 2.45 LMFP-64-2 1.47 2.27 Comparative Example 1 1.43 2.35

[0127] 2. Battery performance test

[0128] The lithium manganese iron phosphate positive electrode materials in each embodiment and comparative example are respectively prepared into batteries, which specifically include the following steps:

[0129] The lithium iron manganese phosphate in each embodiment and comparative example is used as the lithium iron manganese phosphate positive electrode material of the lithium ion battery, and the lithium iron manganese phosphate positive electrode material, conductive carbon black, PVDF and NMP are mixed, and the mixed solution is stirred at a rate of 450r / min for 2h in a ball mill to obtain the positive electrode slurry of the lithium ion battery, and then the above slurry is spread on the aluminum foil through a coating machine, and it is dried at 120°C for 10min, and then the coated pole piece is rolled at 12MPa, and then it is cut and weighed to calculate the mass of the positive electrode active material coated on the pole piece. The pole piece prepared above is glued together with the positive electrode shell by conductive glue to form the positive electrode part of the lithium ion battery, and then the metal lithium sheet is used as the negative electrode, the LiPF6 solution is used as the electrolyte, the concentration of the LiPF6 solution is 0.8M, and the diaphragm is a Celgard2400 microporous membrane. The above materials are assembled into button batteries in a glove box with O2 and H2O contents both lower than 0.1ppm.

[0130] The electrochemical performance of the button cell was tested using the LAND electrochemical test system, with a discharge cut-off voltage of 2.0V and a charge cut-off voltage of 4.3V. The charge and discharge electrochemical performance of the composite manganese iron phosphate lithium positive electrode active material was tested at 25°C and at 0.1C and 1C rates. The charge and discharge curves of the battery prepared from the composite manganese iron phosphate lithium positive electrode material of Examples 1 to 3 of the present invention and Comparative Example 1 at 0.1C are shown in the figure below. Fig.14 As shown; the charge and discharge curves of the battery prepared by the lithium iron manganese phosphate positive electrode materials of Examples 1 to 3 of the present invention and the lithium iron manganese phosphate positive electrode material of Comparative Example 1 at 1C are as shown Fig.15 The electrochemical performance test results of the battery are shown in Table 4.

[0131] Table 4 Battery performance test results

[0132]

[0133] It can be seen from Table 4 that the electrochemical properties of the composite lithium manganese iron phosphate positive electrode materials in each embodiment show a trend of first increasing and then decreasing with the increase of calcination temperature. When the temperature is 750°C, the electrochemical performance of LMFP-46 lithium manganese iron phosphate is the best, that is, the discharge specific capacity of the battery in Example 2 at 0.1C and 1C is 154.82mAh / g and 143.68mAh / g, respectively. Compared with Comparative Example 1, its electrical performance is significantly improved.

[0134] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A composite lithium manganese iron phosphate positive electrode material, characterized in that: A composite material comprising at least two lithium iron manganese phosphate materials having different manganese to iron molar ratios; The molar ratio of manganese to iron in part of the lithium manganese iron phosphate material is 6:4 to 9:1, and the molar ratio of manganese to iron in the remaining part of the lithium manganese iron phosphate material is 1:9 to 4:6; The manganese-iron molar ratio of the composite manganese iron phosphate lithium positive electrode material is 4:6 to 6:

4.

2. The composite lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The lithium manganese iron phosphate material is selected from a first material and a second material; the molar ratio of manganese to iron of the first material is 6:4 to 9:1, and the molar ratio of manganese to iron of the second material is 1:9 to 4:6; The particle size D50 of the first material is 96.6-100.4 nm, and the particle size D90 is 50-150 nm; The particle size D50 of the second material is 288.8-340 nm, and the particle size D90 is 200-350 nm.

3. The composite lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The compaction density of the composite manganese iron phosphate lithium positive electrode material is 2.30-2.6 g / cm 3 ; And / or, the composite manganese iron phosphate lithium positive electrode material has a discharge specific capacity of 131 to 150 mAh / g under 1C conditions and a first efficiency of 92% to 95%.

4. A method for preparing a composite lithium manganese iron phosphate positive electrode material, characterized in that: The following steps are involved: preparing lithium iron manganese phosphate materials with high manganese iron molar ratio and low manganese iron molar ratio respectively; At least two lithium iron manganese phosphate materials with different high and low manganese-iron molar ratios are mixed to obtain a composite lithium iron manganese phosphate positive electrode material with a target manganese-iron molar ratio.

5. The method for preparing the composite lithium iron manganese phosphate positive electrode material according to claim 4, characterized in that: The molar ratio of the high manganese iron is 6:4 to 9:1, and the molar ratio of the low manganese iron is 1:9 to 4:6; and / or The target manganese-iron molar ratio is 4:6 to 6:

4.

6. The method for preparing the composite lithium iron manganese phosphate positive electrode material according to claim 4, characterized in that: Contains at least one of the following features (1) to (2): (1) The mixing process includes mixing with a high-speed mixer at a speed of 1200 to 1800 r / min, and the mixing process lasts for 5 to 10 hours; (2) The steps of preparing lithium iron manganese phosphate materials with high manganese iron molar ratio and low manganese iron molar ratio respectively independently include: preparing a precursor using a carbon source, an iron source, a lithium source, a phosphorus source and a manganese source, and then calcining.

7. The method for preparing the composite lithium iron manganese phosphate positive electrode material according to claim 6, characterized in that: The invention comprises at least one of the following features (1) to (6): (1) The molar ratio of the lithium element in the lithium source, the sum of the manganese element and the iron element in the manganese source and the iron source, and the phosphorus element in the phosphorus source is (0.95-1.08):1:(1-1.05); (2) The mass percentage of the carbon source in the precursor is 3% to 15%; (3) the carbon source comprises at least one of glucose, fructose, sucrose, starch, lactic acid, citric acid, dextrin, chitosan and polyethylene glycol; (4) The raw materials for preparing the precursor further include a doping source, and the doping source includes at least one of a titanium source, a magnesium source, a vanadium source, a nickel source, a niobium source, a zirconium source and a cobalt source; (5) The raw materials for preparing the precursor further include a doping source, the doping source includes a titanium source, and the titanium source includes at least one of titanium dioxide, titanium tetrachloride, titanium nitride, ammonium titanate, ethyl titanate, tetraethyl titanate, butyl titanate, tetraisopropyl titanate, isopropyl titanate and titanium tetraisopropoxide; (6) The raw materials for preparing the precursor further include a doping source, and the doping source includes a titanium source, and the molar amount of the titanium element in the titanium source accounts for 0.5% to 3% of the molar amount of the iron element in the iron source.

8. The method for preparing the composite lithium iron manganese phosphate positive electrode material according to claim 6, characterized in that: Contains at least one of the following features (1) to (4): (1) During the preparation of the lithium manganese iron phosphate material with a high manganese to iron molar ratio, the molar ratio of the manganese source to the iron source is controlled to be 6:4 to 9:1 in terms of manganese element and iron element, respectively; During the preparation of the lithium manganese iron phosphate material with a low manganese to iron molar ratio, the molar ratio of the iron source to the iron source is controlled to be 1:9 to 4:6 in terms of manganese element and iron element, respectively; (2) The method for preparing the precursor specifically comprises: first mixing and sand-milling the carbon source, iron source, lithium source, phosphorus source, manganese source and solvent, and then drying; (3) The calcination treatment includes primary calcination and secondary calcination; the temperature of the primary calcination is 300-600°C, and the time of the primary calcination is 3-10 hours; the temperature of the secondary calcination is 700-900°C, and the time of the secondary calcination is 4-12 hours; (4) The calcination treatment is carried out under protective gas conditions.

9. A positive electrode sheet, characterized in that: The invention comprises the composite lithium iron manganese phosphate positive electrode material according to any one of claims 1 to 3, or the composite lithium iron manganese phosphate positive electrode material prepared by the preparation method of the composite lithium iron manganese phosphate positive electrode material according to any one of claims 4 to 8.

10. A battery, characterized in that: Including the positive electrode sheet as described in claim 9.

Citation Information

Cited By

  • Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof

    CN121076124A